Problems Faced at Supporting and TrainingCourses (STC) and Solution Suggestions According to Teacher Opinions - Fatih Bozbayındır; Mevlüt Kara (Sakarya University Journal of Education)
In this study, the challenges faced in enhancing formal and non-formal education and training courses, the benefits of these courses for stakeholders and solution proposals of teachers for the challenges faced were examined. The study is one of qualitative research methods, was used. The study group of the study was comprised of  48 teachers who teach at ETCs in the Nizip district of Gaziantep province in the academic year of 2015-2016. Semi-structured interview method was used in the present study. The data were analyzed using descriptive and content analyses techniques. A qualitative data analysis program (ATLAS.ti 6) was used in the analysis of the data. According to teachers who teach at ETCs, the most commonly faced challenges are absenteeism, lack of resources for courses, lack of interest in courses due to being provided free of charge and students’ not taking these courses seriously. It was found that the positive contributions of ETCs are that these courses support school courses and teachers financially, promote teachers’ professional development, and help students who are in need financially. Based on teachers’ views, it was suggested that resources must be provided for the ETCs, cooperation must be built with parents, students must be informed about the importance of the courses and a small proportion of money must be taken from the families to hold the ETCs effectively and efficiently.